The nexus between growth, inequality, and poverty: Lessons from long-term Trends in Tanzania, 1961-2017 - Sascha Klocke; Morten Jerven (African Economic History Network (AEHN), 2021)
The lack of secure property rights has been identified by a number of economists - past and present - as an obstacle for long-term growth of output of African farming. The foundation for such a claim is that insecure property rights hinder long-term capital investments. Although the observed infrequency of private property rights in African history is correct there are exceptions. This paper examines one of these exceptions, namely the so-called African Native Purchase farmers in colonial Zimbabwe (Southern Rhodesia from here). The Native Purchase (NP) farmers consisted of a group of Africans that were allowed and able to buy land in specially designated areas. In this paper we analyse the performance of the Native Purchase farmers from their establishment in the 1930s up to 1960, both in terms of output and yields. At first glance, it seems like our case verifies the economic view taken by the proponents of secure property rights. We show that the average NP performed far better than the average African farmer in the Reserve (known as communal land/area after Zimbabwe's independence in 1980). Differently from what one would expect from conventional economic theory the chief differences between the NP and Africans in the reserves was not only capital, but also labour intensity. NP farmers applied more labour-intensive methods than the average farmer in the so-called Native Reserves. Grounded in the factor endowments literature and the concept of interlinked contracts we argue that the relative success of the NP farmers in Southern Rhodesia was largely an outcome of their capacity to use their control over land to access additional labour through share-cropping and tenancy contracts.
Keywords: 330